MICROBABITAT MANAGEMENT WITH VARIOUS REFUGIA PLANTS IN WHITEFLIES (Bemisia tabaci Gennadius) CONTROL ON SEVERAL VARIETIES OF RED CHILI (Capsicum annum L.) - Yunita; Asmanizar; Nurhayati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This research has been conducted in Simalingkar B, Medan Tuntungan Sub-district, Medan, North Sumatra with flat topography. This research started from May to August 2025. This research was supervised by Prof. Dr. Ir. Asmanizar, MP. As the chief supervisor and Prof. Dr. Ir. Nurhayati, MP. as a supervising member. This research is to determine the effect of flowers of tagetes erecta and zinnia sp as refugia plants on the presence of natural enemies of chili plants in controlling whitefly pests and tough varieties, sios tavi and local to whitefly pest attacks. This study used the Separate Plots Design (RPT) research method with two factors, namely refugia and varieties. The first factor consists of 3 levels, namely: R0 = control, R1 = tagetes erecta, R2 = zinnia sp. The second factor of varieties consists of 3 levels, namely: V1 = tough, V2 = sios tavi, R3 = local. The parameters observed were the intensity of Bemisia tabaci attack, natural enemies and production per plot. The results showed that refugia had a significant effect on production per plot, the variety treatment had no significant effect on the intensity of Bemisia tabaci attack and production per plot. The interaction of varieties and refugia had no significant effect on all observations.